Digital tourism branding post-pandemic covid-19 on Twitter: Thailand dan Malaysia case study - Nita Aribah; Suswanta (Faculty of Communications Science, Dr. Soetomo University, 2022)
This study aims to analyse the function of social media as digital tourism branding carried out by Thailand and Malaysia after the COVID-19 pandemic. This research method uses descriptive qualitative methods with the help of the Nvivo 12 Plus application in processing the data. This study uses data from official Twitter social media accounts in Thailand and Malaysia. The results of this study indicate that the analysis of the Twitter conversations of the two accounts shows that the tweets and retweets of @AmazingThailand and @TourismMalaysia are mostly still focused on accounts from their respective domestic regions. The digital tourism branding, which is analysed using marketing communication theory, shows that Thailand and Malaysia have proactive efforts in planning indicators, creation, integration, and marketing strategies. Overall the digital tourism branding efforts carried out by Thailand and Malaysia are quite optimal.